Diverse perennial circular forage systems are needed to foster resilience, ecosystem services, and socioeconomic benefits in agricultural landscapes. Issue 2 (1st July 2022) - Picasso, Valentin D.; Berti, Marisol; Cassida, Kim; Collier, Sarah; Fang, Di; Finan, Ann; Krome, Margaret; Hannaway, David; Lamp, William; Stevens, Andrew W.; Williams, Carol
Abstract: Prevailing agricultural systems dominated by annual crop monocultures, and the landscapes that contain them, lack resilience and multifunctionality. They are vulnerable to extreme weather events, contribute to degradation of soil, water, and air quality, reduce biodiversity, and negatively impact human health, social engagement, and equity. To achieve greater resilience, stability, and multiple ecosystem services therein, and to improve socioeconomic outcomes, we propose a practical framework to gain multifunctionality at multiple scales. This framework includes forages within agroecosystems that have the essential structural features of diversity, perenniality, and circularity. These three structural features are associated with increased resilience, stability, and provision of several ecosystem services, which in turn improve human health and socioeconomic outcomes. This framework improves understanding of, and access to, tools and materials for promoting the adoption of diverse circular agroecosystems with perennial forages. Application of this framework can result in land transformations that solve sustainability challenges in agriculture if policy, economic, and social barriers can be overcome by a transdisciplinary process of equitable knowledge production. Abstract : Prevailing agroecosystems have multiple environmental and socioeconomic problems. Diverse, perennial, circular forage systems (DPCFS) foster resilience to climate change while providing multiple ecosystem services and socioeconomic benefits. A landscape transition from prevailing to DPCFS requires overcoming socioeconomic and policy barriers to adoption while creating enabling conditions through a transdisciplinary process of research and outreach.